98 Effects of rotating-shift work on female sexual function In nurse - two hospitals study. (11th October 2013) - Chen, R Y; Yeh,; Lin,
Abstract : Objective: The main purpose of this study is to examine the impact of night-shift task on the female sexual function, such as sexual desire, arousal, lubrication, orgasm, satisfaction and sexual pain among the female nurses. Method: The study subjects were female nurses who were 20–49 years old and worked in Changhua and Chang Bing Show-Chwan Memorial Hospital. All the study nurses were asked by questionnaire about their time-shift working status, quality of sleep, health status and sexual function. Data were analysed by Statistical Package for Social Science (SPSS). Results: Compared to day-shift nurses, night-shift nurses had a higher risk to have poor sleep quality and self-report health status (p < 0.05). The averaged female sexual function index among the study nurses was 56.42 ± 9.12. There was 68.85% of the study nurses had at least one kind of female sexual dysfunction. The increased age, body mass index, poor sleep quality, and sexual dysfunction of partner were the risk factors of female sexual dysfunction (P < 0.05). The odd ratio of sexual dysfunction of partner was 4.997 (95% CI = -1.341~-8.654; P = 0.008). Conclusion: Night-shift task can cause female nurses to have poor sleep quality, and self reported health status. The female sexual function was also influence by different work and different shift way. The female sexual function was also influence by age, body mass index, partner sexual function, sleep quality and health status.